How often parametrial involvement leads to post-operative adjuvant treatment in locally advanced cervical cancer after neoadjuvant chemotherapy and type C radical hysterectomy?. Issue 8 (August 2015) - Martinelli, F.; Bogani, G.; Ditto, A.; Carcangiu, M.; Papadia, A.; Lecce, F.; Chiappa, V.; Lorusso, D.; Raspagliesi, F.
Abstract Objective Parametrial involvement (PMI) is one of the most important factors influencing prognosis in locally advanced stage cervical cancer (LACC) patients. We aimed to evaluate PMI rate among LACC patients undergoing neoadjuvant chemotherapy (NACT), thus evaluating the utility of parametrectomy in tailor adjuvant treatments. Methods Retrospective evaluation of consecutive 275 patients affected by LACC (IB2-IIB), undergoing NACT followed by type C/class III radical hysterectomy. Basic descriptive statistics, univariate and multivariate analyses were applied in order to identify factors predicting PMI. Survival outcomes were assessed using Kaplan–Meier and Cox models. Results PMI was detected in 37 (13%) patients: it was associated with vaginal involvement, lymph node positivity and both in 10 (4%), 5 (2%) and 12 (4%) patients, respectively; while PMI alone was observed in only 10 (4%) patients. Among this latter group, adjuvant treatment was delivered in 3 (1%) patients on the basis of pure PMI; while the remaining patients had other characteristics driving adjuvant treatment. Considering factors predicting PMI we observed that only suboptimal pathological responses (OR: 1.11; 95% CI: 1.01, 1.22) and vaginal involvement (OR: 1.29 (95%) CI: 1.17, 1.44) were independently associated with PMI. PMI did not correlate with survival (HR: 2.0; 95% CI: 0.82, 4.89); while clinical response to NACT (HR: 3.35; 95% CI: 1.59, 7.04), vaginal involvement (HR: 2.38; 95% CI: 1.12, 5.02) and lymph nodes positivity (HR: 3.47; 95% CI: 1.62, 7.41), independently correlated with worse survival outcomes. Conclusions Our data suggest that PMI had a limited role on the choice to administer adjuvant treatment, thus supporting the potential embrace of less radical surgery in LACC patients undergoing NACT. Further prospective studies are warranted.